Assessment of the Development of Forest-Based Bioeconomy in European Regions - Leire Barañano; Olatz Unamunzaga; Naroa Garbisu; Siebe Briers; Timokleia Orfanidou; Blasius Schmid; Inazio Martínez de Arano; Andrés Araujo; Carlos Garbisu (Sustainability, 2022)
In recent years, the potential of the forest-based bioeconomy to provide competitiveness, differentiation, and sustainability to the European economy has often been claimed. Interestingly, regions, as territorial units with their own political and socioeconomic strategies, have been highlighted as the most suitable targets for the development of the European forest-based bioeconomy. Here, using the case method, we evaluated the development of the forest-based bioeconomy in three European regions (i.e., North Karelia in Finland, North Rhine-Westphalia in Germany, the Basque Country in Spain), by appraising the status of 10 previously identified key drivers through primary (interviews with experts) and secondary (literature review) sources of information. In our analysis, North Karelia and the Basque Country obtained the highest and lowest score, respectively, with regard to forest-based bioeconomy development. In any case, for the successful development of the forest-based bioeconomy in a European region, it is essential to accept the unnegotiable, critically, of the long-term sustainability of forest bioresources and production processes, as well as the need to foster the required changes in consumption patterns.